1987
DOI: 10.1021/ja00250a044
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of carbon monoxide to methane and ethylene at a copper electrode in aqueous solutions at ambient temperature and pressure

Abstract: Carbon monoxide is a substance of primary importance from the viewpoint of utilization of carbon resources. Hydrogenation of CO in the gas phase has been widely studied, but only a small number of papers has been published about electrochemical reduction. Electroreduction of CO did not proceed effectively according to the previous papers;1 the cathodic partial currents for electroreduction of CO were very small, not exceeding 5 X 10"5 A cm"2. We briefly describe here an electroreduction of CO at a Cu cathode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
256
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(273 citation statements)
references
References 0 publications
16
256
0
1
Order By: Relevance
“…Although the conversion mechanism of CO 2 to liquid fuels is not very clear at present but it is widely accepted that CO 2 is first reduced to CO and then it is further converted to alcohols and other hydrocarbons through multistep electron transfer pathways. Earlier studies have found that CO reduction on Cu results in similar products as obtained from CO 2 reduction, proposing that CO was an intermediate in the reduction of CO 2 (44)(45)(46).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although the conversion mechanism of CO 2 to liquid fuels is not very clear at present but it is widely accepted that CO 2 is first reduced to CO and then it is further converted to alcohols and other hydrocarbons through multistep electron transfer pathways. Earlier studies have found that CO reduction on Cu results in similar products as obtained from CO 2 reduction, proposing that CO was an intermediate in the reduction of CO 2 (44)(45)(46).…”
Section: Introductionmentioning
confidence: 70%
“…Polycrystalline Cu foil had shown lower current densities and H 2 was the only detectable product under these similar conditions. Another study has shown 22% total Faraday efficiency for CO reduction at very negative potentials (around −0.7 V vs. RHE) and its Faraday efficiency for oxygenates was only 7% (45). A maximum of 65% Faraday efficiency from CO reduction have been reported for polycrystalline copper foil at −0.9 V vs. RHE but Faraday efficiency of oxygenates was only 10% (70).…”
Section: R E T R a C T E Dmentioning
confidence: 98%
See 2 more Smart Citations
“…8,9 Thus, CORR determines the overpotentials and selectivities for additionally reduced products from CO 2 RR, so we focus here on CORR. Cu(111) serves as a model electrocatalyst that delivers the essential chemistry of CORR, 10 and it has been confirmed to be stable under electrochemical working conditions, 11 so we focus here on CORR on Cu(111).…”
Section: ■ Introductionmentioning
confidence: 99%